Pelaksanaan Nasional Health Insurance Pada Aspek Kepesertaan Untuk Mencapai Universal Health Coverage: The Implementation of National Health Insurance on The Aspect of Participation to Achieve Universal Health Coverage - Syifa Shidqi Putri; Chriswardani Suryati; Nurhasmidar Nandini (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
National Health Insurance in a country is a program to achieve Universal Health Coverage which ensures that every citizen in the population has access to health services. The existence of mandatory NHI membership rules makes participation a very important aspect. In the development of the implementation of NHI, there was a phenomenon of decreasing participation which became the reason for researchers to research to analyze factors related to NHI participation, obstacles, and efforts made to maintain and increase participation. This research is a type of Literature Review research with a simple data analysis method (simplified approach). There are 12 national articles and 8 international articles that have been selected by researchers as research material. The results showed that the factors related to NHI participation were divided into 3 main factors, namely predisposing factors, enabling factors, and needs factors. The predisposing factors include age, gender, education, occupation, and the number of family members. Enabling factors include knowledge, income/income, and family support. Meanwhile, the need factor contains perception and motivation factors. In addition to finding factors, this study also found obstacles that affect participation in NHI, and efforts that can improve aspects of NHI participation.